Pengaruh Perbedaan Jenis Lahan dan Terapan Budidaya Terhadap Produksi Jambu Air Merah Delima - Miranti Dian Pertiwi, Djoko Prajitno, dan Dja’far Shiddieq (Jurnal Ilmu Pertanian, 2012)
ABSTRACTMerah Delimais considered as superior native variety of water apple in Demak. The fruitis wellknown as the high quality water apple  in theregions. Suitable environment of climate,topography and soil physic chemical properties in Demak make it possible for the fruit to produce more than twice per year with attractive physical appearance of the fruit as redand shiny color, large, sweet, crispy and high economic value. However, researches of Merah Delima water apple were still limited compared to other fruit superior commodities. Therefore, the survey as assessment method of water apple was conducted to identify and study the differences of cultivation, growth and production of the fruits which were cultivated in dryland and paddy fields as specific conditions of Demak regency. The assessmentseries included pre-survey in October 2011 – January 2012 and plant’s observation in March –June 2012 which was a peak season for the fruits. The site locations were chosen purposively ,i.e. in Wonosalam, Demak and Bonang Sub Districts. Inthatcase, water apple tree’s population differences were being the criteria of sites selection. Inpresurvey, as many as 50 farmers were interviewed as respondents with the proportion of consecutive 28 : 14 : and 8 farmers for each Sub District. The plant’s observation included 54 trees which were chosen purposively. ‘Nested design’ was used (3 subdistrict x 2 land types x 3 plants). Basically the cultivation results were compared to Water Apple Standard Operating Procedures (SOP) issued by Demak Agriculture Services. Parameters observed in the survey involved physical and chemical properties of soil, microclimate, growth, production and quality of water apple. The results showed that water apple cultivation applied statuses in dry and paddy field were only in low and medium, based on Water Apple Standard Operating Procedures (SOP). Infact, there were significant interaction effect between land types and cultivation applied as well as between the land types and cultivation applied in Merah Delima Water Apple production. Water Apple cultivation in surjan system or integrated with fish – farming system were less suitable since most of the time the roots were under anaerobic condition. Water apple cultivationis more suitable in flat land within termittent irrigation system since soil moisture was not relatively high. In Grumosol soi ltype, available soil moisture is considered as one of soil physical properties that has negative significant effect for Merah Delima water apple production, both in dry land and paddy field. In that case, the higher available soil moisture the lower water apple Merah Delima production.Key words: Merah Delima Water apple, cultivation, dry land, paddy field, Demak SubDistrict